P2X1 ion channel deficiency causes massive bleeding in inflamed intestine and increases thrombosis. (10th September 2019) - Wéra, Odile; Lecut, Christelle; Servais, Laurence; Hego, Alexandre; Delierneux, Céline; Jiang, Zheshen; Keutgens, Aurore; Evans, Richard J.; Delvenne, Philippe; Lancellotti, Patrizio; Oury, Cécile
Abstract: Background: Intestinal inflammation is associated with bleeding and thrombosis, two processes that may involve both platelets and neutrophils. However, the mechanisms and the respective contribution of these cells to intestinal bleeding and extra‐intestinal thrombosis remain largely unknown. Objective: Our study aimed at investigating the mechanisms underlying the maintenance of vascular integrity and thrombosis in intestinal inflammation. Methods: We used a mouse model of acute colitis induced by oral administration of dextran sodium sulfate (DSS) for 7 days. Bleeding was assessed after depletion of platelets, neutrophils, or glycoprotein VI (GPVI); treatment with aspirin or clopidogrel; or in P2X1‐deficient mice. Extra‐intestinal thrombosis was analyzed using a laser‐induced injury model of thrombosis in cremaster muscle arterioles. Results: Platelet depletion or P2X1 deficiency led to macrocytic regenerative anemia due to intestinal hemorrhage. In contrast, GPVI, P2Y12, and thromboxane A2 were dispensable. Platelet P‐selectin expression and regulated on activation, normal T‐cell expressed and secreted (RANTES) plasma levels were lower in DSS‐treated P2X1‐deficient mice as compared to wild‐type mice, indicative of a platelet secretion defect. Circulating neutrophils had a more activated phenotype, and neutrophil infiltration in the colon was increased. P2X1‐deficient mice also had elevated plasma granulocyte‐colony stimulating factor (G‐CSF) levels. Neutrophil depletion limited blood loss in these mice, whereas exogenous administration of G‐CSF in colitic wild‐type mice caused macrocytic anemia. Anemic colitic P2X1‐deficient mice formed atypical neutrophil‐ and fibrin‐rich, and platelet‐poor thrombi upon arteriolar endothelial injury. Conclusions: Platelets and P2X1 ion channels are mandatory to preserve vascular integrity in inflamed intestine. Upon P2X1 deficiency, neutrophils contribute to bleeding and they may also be responsible for enhanced thrombosis.